Fine-Tuning Brand Endorsements: Exploring Race-Sport Fit with Athlete Endorsers - Youngmin Yoon; Jun Woo Kim; Mar Magnusen; Michael Sagas (Journal of Applied Sports Management, 2018)
The present study examines the effect of an athlete endorser’s race-sport fit in the decision-making process of athlete endorsed product selection. The results of this study reveal that the race of athlete endorsers can influence endorsement strategies depending on the sport associated with the athlete endorser. Perceived race-sport fit was also a key factor in creating both positive sport consumer attitudes and increased purchase intentions toward an athlete endorsed product. The findings of this study should be beneficial to athletes and sport business professionals when considering endorsement strategies for sport-related products and brands. Subscribe to JASM
Keywords: Culture; identification; marketing; sponsorship; sport fans